THE IMPACT OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE AND CUSTOMER IN THE CAMBODIAN HAIRDRESSING INDUSTRY - Khath, Bora (UTSAHA: Journal of Entrepreneurship, 2024)
This study investigates the impact of transformational leadership on employee performance job satisfaction, and customer satisfaction within the Cambodian hairdressing industry. By analyzing secondary data from various studies, key findings indicate that transformational leadership practices, such as inspirational motivation, individualized consideration, intellectual stimulation, and ideal influence, significantly enhance employee morale and productivity. Employees perceive these leadership behaviors positively, resulting in higher job satisfaction and improved service quality. The study also provides practical recommendations for salon owners to adopt transformational leadership strategies effectively, including defining clear vision and goals, offering individualized support, encouraging innovation, leading by example, and recognizing employee achievements. While relying on secondary data presents certain limitations, this research underscores the need for primary data collection to gain more nuanced insights. Future research should include employee surveys and interviews, longitudinal studies, and cross-cultural comparisons to explore the long-term effects and broader applicability of transformational leadership practices in service industries. These findings have significant implications for salon management, highlighting the potential of transformational leadership to drive business success in competitive markets. This study aims to offer actionable insights for salon owners and set the stage for further exploration of leadership practices in the Cambodian context.